2021
DOI: 10.3390/s21144868
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Load Plates Diameters, Shapes of Columns and Columns Spacing on Results of Load Plate Tests of Columns Formed by Dynamic Replacement

Abstract: The dynamic replacement method is used to strengthen the subgrade of objects, usually up to 5 to 6 m thick. After the improvement process, acceptance tests in the form of load testing are carried out. Interpretation of the test results can cause some difficulties. Dynamic replacement results in a situation where columns of different shapes, loaded with plates of diameters usually smaller than the head diameter and in the vicinity of adjacent columns, are subjected to load tests. In order to demonstrate the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…The shapes of the columns formed by the dynamic replacement technique in the field conditions have been studied by one of the authors since 2007. The total of 65 endbearing and floating columns were investigated [5,8,11]. It has been noticed that certain relationships exist between the shapes of the end-bearing columns and the ratio of the thickness of the soft soil layer (𝐻 𝑠 ) to the height of the used pounder (𝐻 𝑝 ) [9].…”
Section: Shapes Of the Dr Columns In Situmentioning
confidence: 99%
See 1 more Smart Citation
“…The shapes of the columns formed by the dynamic replacement technique in the field conditions have been studied by one of the authors since 2007. The total of 65 endbearing and floating columns were investigated [5,8,11]. It has been noticed that certain relationships exist between the shapes of the end-bearing columns and the ratio of the thickness of the soft soil layer (𝐻 𝑠 ) to the height of the used pounder (𝐻 𝑝 ) [9].…”
Section: Shapes Of the Dr Columns In Situmentioning
confidence: 99%
“…The maximum final length of a typical end-bearing column is usually 5-7 m [4,6,7]. The in situ measurements of the as-built columns, conducted by one of the authors [5,8,9], proved that the ground conditions have a great influence on the final shape of the columns. One of the most important factors is the ratio of the soft soil layer thickness and the height of the pounder.…”
Section: Introductionmentioning
confidence: 99%
“…One involves case studies providing only the basic information on the diameters and lengths [4], [18][19][20][21], where the diameters were usually measured at the terrain level. The second group is less numerous and comprises articles where the column shapes and dimensions are determined directly from the measurements of the excavated columns [15], [22][23][24][25], or indirectly from penetration tests [5], [26] or geophysical survey [27]. Table 1 presents the summary of the literature review including the observed shapes of the columns, the D c /D p ratios and the ground profiles at the sites.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kwiecień and Sękowski [24] identified up to five different shapes, which confirms the specific nature of this technology in relation to the other methods of column formation, where the columns are mainly cylindrical [16,17]. Kwiecień [15] indicated the influence of the soil thickness (expressed as the ratio of the weak soil thickness H s to the pounder height H p ) on the end-bearing columns' shapes: the shape of the columns changed from a cylinder (for H s /H p = 1), through a truncated cone (H s /H p = 1-1.5), a barrel (H s /H p = 1.5-2.0) and asymmetrical barrel (H s /H p = 2-2.5). For the floating columns three common shapes were identified: a cylinder, a barrel and an inverted truncated cone (regardless of the H s /H p ratio).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation